Management by objectives in European public employment services - Hugh Mosley; Holger Schütz; Nicole Breyer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
This paper surveys and compares national experience with performance management in European public employment services (PES) in the form of 'management by objectives' (MBO). Part I of this paper reviews the relevant performance management literature and defines key terms. Part II presents the results of a stocktaking survey of the use of operational objectives, performance indicators, benchmarking and related managerial practices in all 15 EU Member States and Norway. Part III reports the results of a comparative analysis and more in-depth assessment of national experience with management by objectives in Austria, France, Great Britain, and Sweden. Part IV summarizes principal findings and presents main conclusions. Ten of the eighteen PES organizations surveyed were found to use management by objectives: Austria, Denmark, the Flanders regional PES (VDAB) in Belgium, France, Germany, Great Britain, Finland, the Netherlands, Norway, and Sweden. In summary, the impact of MBO-systems depends strongly on design and implementation features. If based on principles of 'good-practice', MBO can improve the efficiency and effectiveness of PES operations. – – In diesem Papier wird eine Bestandsaufnahme zu Verbreitung und Praxis der Zielsteuerung (Management by Objectives, MBO) in europäischen Arbeitsverwaltungen vorgelegt. Teil I rekapituliert die relevante Forschungsliteratur und entwirft einen analytischen Bezugsrahmen. In Teil II wird ein empirischer Überblick zur Steuerung mittels Zielen und Indikatoren in europäischen Arbeitsverwaltungen gegeben. Unter 18 Arbeitsverwaltungen sind Zielsteuerungsansätze für die zehn Länder Dänemark, Deutschland, Finnland, Flandern (VDAB), Frankreich, Großbritannien, Niederlande, Norwegen, Österreich, und Schweden nachzuweisen. Teil III vergleicht vertiefend die Managementansätzen in den Arbeitsverwaltungen Österreichs, Großbritanniens, Frankreichs und Schwedens. Für den Erfolg (oder Mißerfolg) der Zielsteuerung sind Design- und Implementationsfaktoren entscheidend. Wenn Prinzipien 'guter Praxis' beachtet werden, kann die Effektivität und Effizienz der Arbeitsverwaltung mittels MBO gesteigert werden.
Keywords: 330; Arbeitsverwaltung; Kooperative Führung; Erfolgsfaktor; Westeuropa; Österreich; Großbritannien; Schweden; Frankreich